Cytochrome P450‐mediated metabolism of the synthetic cannabinoids UR‐144 and XLR‐11. Issue 8 (11th September 2015) - Nielsen, Line Marie; Holm, Niels Bjerre; Olsen, Lars; Linnet, Kristian
Abstract : In recent years, synthetic cannabinoids have emerged in the illicit drug market, in particular via the Internet, leading to abuse of these drugs. There is currently limited knowledge about the specific enzymes involved in the metabolism of these drugs. In this study, we investigated the cytochrome P450 (CYP) enzymes involved in the metabolism of the two synthetic cannabinoids (1‐pentyl‐1 H ‐indol‐3‐yl)‐(2, 2, 3, 3‐tetramethylcyclopropyl)methanone (UR‐144) and [1‐(5‐fluoropentyl)‐1 H ‐indol‐3‐yl)](2, 2, 3, 3‐tetramethylcyclopropyl)methanone (XLR‐11). This study extends previous studies by identifying the specific CYP enzymes involved in the metabolism of UR‐144 and XLR‐11 utilizing a panel of nine recombinant enzymes (CYP1A2, 2B6, 2C8, 2C9, 2C18, 2C19, 2D6, 3A4, and 2E1). This is followed by an investigation of the effect of specific inhibitors targeted against CYP1A2, 2B6, 2C9, 2C19, 2D6 and 3A4 in human liver microsomes (HLM). Incubations of UR‐144 and XLR‐11 with recombinant CYP enzymes revealed that UR‐144 and XLR‐11 are extensively metabolized by CYP3A4 at the tetramethylcyclopropyl (TMCP) moiety, but also CYP1A2 and CYP2C19 showed activity. Inhibition of CYP3A4 in HLM attenuated the metabolism of UR‐144 and XLR‐11, while inhibition of the other CYP enzymes in HLM had only minor effects. Thus, CYP3A4 is the major contributor to the CYP mediated metabolism of UR‐144 and XLR‐11 with minor contributions from CYP1A2. Users of UR‐144 and XLR‐11 are thus subject to the influence of potential drug‐drug interactions, if they are concomitantly medicated with CYP3A4 inducers (e.g. some antiepileptics) or inhibitors (e.g. some antifungal drugs). Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Use of synthetic cannabinoids has been known since 2004, however little is known about the enzymes involved the metabolism. Herein we investigate the cytochrome P450 enzymes involved in the metabolism of the synthetic cannabinoids UR‐144 and XLR‐11. CYP3A4 is the major contributor to the cytochrome mediated metabolism of UR‐144 and XLR‐11 with minor contributions from CYP1A2.